Advantages and problems of foliation in the educational process from modern information technologies - Kayimova Shakhzoda Vohid kizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article provides information about the effectiveness of the media and the problems encountered in its use. Particular attention is paid to the concept of educational technologies. It is covered about the role of the modern educational process in professional activity, its importance in personnel training. It is covered about what qualities today's grown-up specialists will have. The introduction of Information Technology was reflected on practical problems and achievements in the optimization of the educational process. The work on information security in our country has been discussed. The work of professors in Russia on the application of Information Technology in education is mentioned. Information about spatial gaps in education is provided. The strategy of innovative development of higher professional education in Russia was mentioned.